2014
DOI: 10.1136/neurintsurg-2014-011152
|View full text |Cite
|
Sign up to set email alerts
|

Is long-term follow-up of adequately coil-occluded ruptured cerebral aneurysms always necessary? A single-center study of recurrences after endovascular treatment

Abstract: Most aneurysms adequately occluded at 6 months did not show evidence of late recurrence. Large and wide-neck aneurysms are, however, at greater risk of later recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…A small number of papers have reported recurrence and / or retreatment of ruptured cerebral aneurysm after coiling in relation to the location of the aneurysm. [3][4][5][6] Although the long-term stability of aneurysm occlusions has improved over time, the rate of recurrence differs with various aneurysm locations. High recurrence rates for an IC-PC aneurysm and a BA aneurysm have been reported, but no report has described a high recurrence rate for a coiled ruptured proximal IC aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of papers have reported recurrence and / or retreatment of ruptured cerebral aneurysm after coiling in relation to the location of the aneurysm. [3][4][5][6] Although the long-term stability of aneurysm occlusions has improved over time, the rate of recurrence differs with various aneurysm locations. High recurrence rates for an IC-PC aneurysm and a BA aneurysm have been reported, but no report has described a high recurrence rate for a coiled ruptured proximal IC aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) The rate of aneurysm recurrence is also related to the location of the aneurysm. [3][4][5][6] An internal carotid artery-posterior communicating artery (IC-PC) aneurysm and a basilar artery (BA) tip aneurysm showed a 9.3%-55% recurrence rate. 3,5,6) Advances in technology have continued to decrease the rate of recurrence of a coiled aneurysm from 8.8% to 4.8%.…”
mentioning
confidence: 99%
“…The present study analyzed a group in which no significant differences were apparent between the recurrence group and stable group in aneurysm size , wide neck, or low coil packing ratio, all of which have previously been considered as factors potentially associated with recurrence after endovascular treatment [ 1 , 2 , 3 , 4 , 5 , 14 , 15 , 16 ]. As a VER 20% has been reported to be a significant factor for recurrence, the present study selected cases with VER 20% for analysis [ 1 , 3 , 4 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it was demonstrated in the International Subarachnoid Aneurysm Trial (ISAT), angiographic occlusion rates of coiling in long-term follow-up are worse than the rates for microsurgical clipping [26]. Hence, the imaging follow-up after endovascular treatment is mandatory [27]. It is reported that the majority of adequately coil-occluded cerebral aneurysms at initial follow-up of 6 months do not require further imaging follow-up [27].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the imaging follow-up after endovascular treatment is mandatory [27]. It is reported that the majority of adequately coil-occluded cerebral aneurysms at initial follow-up of 6 months do not require further imaging follow-up [27]. Therefore, we perform routinely first follow-up angiography at 6 month after initial treatment and in cases of complete aneurysms obliteration we do not follow-up patients any longer.…”
Section: Discussionmentioning
confidence: 99%